EFFECT OF PROPOLIS HONEY CANDY CONSUMPTION ON THE ACTIVITY OF LACTOPEROXIDASE IN STIMULATED SALIVA - RAHMI, SYARIFAH; SARWONO, AGOENG TJAHAJANI; SOEKANTO, SRI ANGKY (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to analyze the effect of propolis honey candy consumption on lactoperoxidase (LPO) activity in stimulated saliva. Methods: Stimulated saliva samples were collected from subjects before and after propolis honey candy consumption twice a day for 7 days, and the LPO activity was measured by optical density using a microplate reader. Results: The LPO activity before and after propolis honey candy consumption was found to be 0.010 and 0.013, respectively. Conclusions: A statistically significant increase in the LPO activity after propolis honey candy consumption was observed (Wilcoxon test; p <0.05).